Scottish Slave-owners in Suriname: 1651–1863. Issue 1 (May 2018) - Alston, David
Abstract : This is an account of Scots in the Dutch colony of Suriname from 1651 until the emancipation of slaves in the Dutch Empire in 1863, when Scottish owners of slaves received nine per cent of the compensation paid to slave-owners in the colony by the Dutch Government. Before 1790 the small Scots presence in Suriname was a product of the outward looking nature of the Dutch Atlantic and the willingness of some Scots, most with with family, religious or military ties to the Netherlands, to seize the opportunities this offered. After 1790 the British presence in Suriname expanded, with a significant involvement of Highland Scots who came to work new plantations in the colony from the neighbouring British controlled colonies of Berbice and Demerara. After the emancipation of slaves in the British Empire in 1834, a number of these Scottish slave-owners campaigned against emancipation in the Dutch Empire. Despite buying and selling slaves in breach of British law, and despite public criticism, none of these British-based slave-owners were prosecuted. The article concludes with an examination of the legacies of this Scottish slave-ownership, both in Scotland and in Suriname.